2020
DOI: 10.1097/01.reo.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Measures in Older Cancer Survivors: An Examination of Reliability, Validity, and Minimal Detectable Change

Abstract: Background: Cancer and its treatment contribute to multiple sequelae affecting physical function, including difficulty in balance and walking. Although clinical tests should be used to assess fall risks in older cancer survivors, the literature describing the validity, reliability, measurement error, and minimal detectable change (MDC) of mobility measures is lacking. Objective: The purpose of this study was to describe the reliability, validity, standard error of the measurement (SEM), and minimal detectable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Older cancer survivors ages 65 years and above were recruited from the community as a part of a larger study[ 32 ]. Recruitment occurred through advertisements, flyers, and word-of-mouth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Older cancer survivors ages 65 years and above were recruited from the community as a part of a larger study[ 32 ]. Recruitment occurred through advertisements, flyers, and word-of-mouth.…”
Section: Methodsmentioning
confidence: 99%
“…Timing began when the tester said “go” and ended when the participant’s body made contact with the chair. The TUG test has established validity and test-retest reliability in older cancer survivors[ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants in this study were selected from a larger study of mobility, balance, and cognitive measures in community-dwelling older cancer survivors. 9,17 Inclusion criteria for that study included being age of 65 years or more, English speaking, having a medically confirmed diagnosis of breast, lung, prostate or colorectal cancer, primary cancer treatment completion at least 3 months prior to testing, and being able to get up from a chair, stand, and walk 50 ft with or without the use of an assistive device. Only data from breast cancer survivors were used in this analysis as they comprised the majority of the sample population.…”
Section: Methodsmentioning
confidence: 99%
“…14,16 Two additional versions of the TUG exist which have been used to predict falls, including the TUG-Cognitive where a secondary cognitive task is performed during the measure, and the TUG-Manual. Similar to GS, the validity and reliability of the 3 TUG measures have been established in older cancer survivors, 9 but the prognostic ability to predict falls and the cut-off scores with the highest sensitivity and specificity have not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation